Impact of weed management practices on weed control efficiency and fibre quality in cotton under the high-density planting system - Nageswari, R; Sanjay Kumar, T; Anitha, R; Dhanushkodi, V; Sujatha, K B; Satheeshkumar, N; Rajarathinam, P; Somasundaram, S; Rathika, S; Ramesh, T (Plant Science Today, 2025)
Cotton enjoyed the synonyms ‘White Gold,’ ‘King of Fibre Crops,’ and ‘Friendly Fibre’, playing a vital role as both a cash and fibre crop in India. However, weeds pose a major challenge, causing an approximate 45% yield reduction in cotton nationwide. Effective weed management is crucial for optimizing cotton yield and fibre quality. This study evaluated the impact of various weed management practices on productivity and fibre quality. Field trials were conducted using multiple treatments, including pre-and post-emergence herbicides, hand weeding, and power weeding. Fibre quality parameters, such as fibre length, strength, fineness, micronaire, and elongation percentage, were measured across treatments. While results showed no significant differences in fibre quality among the treatments, the combination of preemergence (PE) application of Pendimethalin at the rate of 1.0 kg active ingredient ha-1 + Metolachlor at the rate of 1.0 kg active ingredient ha-1 followed by post-emergence (POE) application of Pyrithiobac sodium at the rate of 0.075 kg active ingredient ha-1 + quizalofop ethyl at the rate of 0.075 kg active ingredient ha-1 emerged as the most effective weed control strategy.This treatment provided effective weed suppression, reduced competition for resources, and resulted in a higher seed cotton yield than other treatments. The study concluded that, although fibre quality did not vary significantly, the integrated use of Pendimethalin and Metolachlor as preemergence herbicides and Pyrithiobac sodium and quizalofop ethyl as post-emergence herbicides offers an optimal solution for cotton growers.